Graphic Novels for Children and Young Adults : A Collection of Critical Essays - Tarbox, Gwen Athene; Abate, Michelle Ann, 1975- (Book collections on Project MUSE., 2017)
"One of the most significant transformations in literature for children and young adults during the last twenty years has been the resurgence of comics. Educators and librarians extol the benefits of comics reading, and increasingly, children's and YA comics and comics hybrids have won major prizes, including the Printz Award and the National Book Award. Despite the popularity and influence of children's and YA graphic novels, the genre has not received adequate scholarly attention. Graphic Novels for Children and Young Adults is the first book to offer a critical examination of children's and YA comics. The anthology is divided into five sections, structure and narration; transmedia; pedagogy; gender and sexuality; and identity, that reflect crucial issues and recurring topics in comics scholarship during the twenty-first century. The contributors are likewise drawn from a diverse array of disciplines -- English, education, library science, and fine arts. Collectively, they analyze a variety of contemporary comics, including such highly popular series as Diary of a Wimpy Kid and Lumberjanes; Eisner award-winning graphic novels by Gene Luen Yang, Nate Powell, Mariko Tamaki, and Jillian Tamaki; as well as volumes frequently challenged for use in secondary classrooms, such as Raina Telgemeier's Drama and Sherman Alexie's The Absolutely True Diary of a Part-Time Indian."--